Assessment of carbon sequestration for environmental conservation at the Manuel Félix López Higher Polytechnic School of Agriculture of Manabí (ESPAM MFL) (Research, Society and Development, 2025)
Currently, carbon sequestration is one of the alternatives to combat the increase in CO2, thanks to the environmental and economic benefits it provides. The purpose of this study is to assess carbon sequestration for environmental conservation at ESPAM-MFL in the agroindustrial, CIIDEA, and polytechnic forest areas. The research was non-experimental with a descriptive-quantitative approach, as dasometric data obtained in the field were measured and recorded, such as the height and DBH of the individuals. Based on these parameters, allometric equations were applied to estimate forest biomass and the carbon and CO2 stored in the trees. The results indicated a total of 794 tree individuals distributed across 392 CIIDEA trees, 323 Polytechnic Forest trees, and 79 Agroindustrial areas. The most representative species on campus was mahogany (Swietenia macrophylla), with a total of 229 individuals. The carbon stored was determined to be 162.93 t/ha, of this figure, the Polytechnic Forest leads with 138.07 t/ha (84.7%), CIIDEA with 20.91 t/ha (12.8%), and Agroindustrial with 3.96 t/ha (2.4%). The estimated CO₂ equivalent stored was 597.95 t/CO₂/year/ha. The Polytechnic Forest contributes 506.71 t/CO₂/year/ha (84.7%), CIIDEA 76.73 t/CO₂/year/ha (12.8%), and the Agroindustrial Area 14.52 t/CO₂/year/ha (2.4%). The Polytechnic Forest was the largest contributor to carbon sequestration among the areas studied, and is therefore considered the most ecologically important area in terms of carbon sequestration.